The disclosure of media framing between bloggers in Malaysia / Muhammad Hakimi Tew Abdullah, Abdul Latiff Ahmad and Hoo Fang Jing - Abdullah, Muhammad Hakimi Tew; Ahmad, Abdul Latiff; Hoo, Fang Jing (Centre for Media and Information Warfare Studies, 2017)
The influence of blog is extensively noticeable especially during the 13th General Election that had received unexpected turn outs as the public nowadays are more daring and bolder in voicing their opinions on the democratic issues in Malaysia. Malaysians are now more outspoken and have cried out for a new government by asking the current government who has been ruling since independence to step down. Most blogs that are supporting the oppositions have voiced out the intention to call upon a new government through campaigns such as "Ubah" and "Ini Kalilah". The effects of this have brought to a new dynamic in the pursuit of each political party in Malaysia to fight for various ideologies and move towards victory for the party that they represent. This research paper is to explain on the disclosure of a generic frame by bloggers in Malaysia before and after the 13th General Election. It has involved two groups of blogger represented by the Pro-Barisan Nasional and the Pro-Pakatan Rakyat. A quantitative content analysis and an in-depth interview were done in explaining the media frame that both groups of blogger had used. The findings portray the usage of media frames from both groups of blogger in achieving their main goals for the benefits of everyone. However, the economic consequences frame has shown as having the lowest impact due to the facts that it has its own characteristics that needed expertise to discuss further on the economic issues in Malaysia